Comprehensive proteome analysis of human skeletal muscle in cachexia and sarcopenia: a pilot study. Issue 4 (15th March 2017) - Ebhardt, H. Alexander; Degen, Simone; Tadini, Valentina; Schilb, Alain; Johns, Neil; Greig, Carolyn A.; Fearon, Kenneth C.H.; Aebersold, Ruedi; Jacobi, Carsten
Abstract: Background: Cancer cachexia (cancer‐induced muscle wasting) is found in a subgroup of cancer patients leaving the patients with a poor prognosis for survival due to a lower tolerance of the chemotherapeutic drug. The cause of the muscle wasting in these patients is not fully understood, and no predictive biomarker exists to identify these patients early on. Skeletal muscle loss is an inevitable consequence of advancing age. As cancer frequently occurs in old age, identifying and differentiating the molecular mechanisms mediating muscle wasting in cancer cachexia vs. age‐related sarcopenia are a challenge. However, the ability to distinguish between them is critical for early intervention, and simple measures of body weight may not be sufficiently sensitive to detect cachexia early. Methods: We used a range of omics approaches: (i) undepleted proteome was quantified using advanced high mass accuracy mass spectrometers in SWATH‐MS acquisition mode; (ii) phospho epitopes were quantified using protein arrays; and (iii) morphology was assessed using fluorescent microscopy. Results: We quantified the soluble proteome of muscle biopsies from cancer cachexia patients and compared them with cohorts of cancer patients and healthy individuals with and without age‐related muscle loss (aka age‐related sarcopenia). Comparing the proteomes of these cohorts, we quantified changes in muscle contractile myosins and energy metabolism allowing for a clear identification of cachexia patients. In an in vitro time lapse experiment, we mimicked cancer cachexia and identified signal transduction pathways governing cell fusion to play a pivotal role in preventing muscle regeneration. Conclusions: The work presented here lays the foundation for further understanding of muscle wasting diseases and holds the promise of overcoming ambiguous weight loss as a measure for defining cachexia to be replaced by a precise protein signature.